Controversies in globalization : contending approaches to international relations - Haas, Peter M.; Hird, John A. (Thousand Oaks, California : CQ Press, 2016)
Debate-style readers can be effective and provocative teaching tools in the classroom. But if the readings are not in dialogue with one another, the crux of the debate is lost on students, and the reader fails to add real depth to the course. This book solves this issue by inviting 15 pairs of scholars and practitioners to address current and relevant questions in international relations through brief'yes' and'no' pieces.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 21, 2016).
Keywords: Globalization